Science Mapping of the Global Knowledge Base on Management, Leadership, and Administration Related to COVID-19 for Promoting the Sustainability of Scientific Research - Karakose, Turgut; Yirci, Ramazan; Papadakis, Stamatios; Ozdemir, Tuncay Yavuz; Demirkol, Murat; Polat, Hakan (Mdpi, 2021)
The pandemic caused by the COVID-19 virus has resulted in inevitable radical changes across almost all areas of daily life, with the pandemic having revealed perhaps the greatest crisis humanity has faced in modern history. This study aims to provide thematic and methodological recommendations for future sustainable research programs through a bibliometric analysis of publications focused on management, leadership, and administration related to COVID-19. The data for the study were obtained from the Web of Science Core Collection (WoSCC) bibliographic database and then analyzed according to thematic content analysis and bibliometric methodology. The study's units of analysis include countries, journals, keywords, research models, sample/study group, and time to publication. VOSviewer software and visualization maps were used to report the findings obtained from the analyzed data. When the study's results are evaluated regarding the number of related publications and total citations, it can be revealed that Anglo-American-, Chinese-, and European-centered dominance continues in COVID-19-related studies. The vast majority of publications on this subject area are concentrated in the field of health. In addition, the study's findings revealed that the examined articles were generally published in journals considered as prestigious, have high impact factors, are published in the English language, and with articles published in a short time after a much-reduced editorial/review and publishing process. Unlike previous bibliometric reviews, this research comprehensively analyzed the management-, leadership-, and administration-oriented publications related to COVID-19 with a holistic approach, providing essential findings and recommendations for future sustainable thematic research opportunities.
Keywords: COVID-19; coronavirus; bibliometric analysis; visualization; management; leadership; administration; sustainability